Exploring Trait Trade-Offs for Fungal Decomposers in a Southern California Grassland - Alster, Charlotte J.; Allison, Steven D.; Glassman, Sydney I.; Martiny, Adam C.; Treseder, Kathleen K. (Frontiers in Microbiology, 2021)
Fungi are important decomposers in terrestrial ecosystems, so their responses to climate change might influence carbon (C) and nitrogen (N) dynamics. We investigated whether growth and activity of fungi under drought conditions were structured by trade-offs among traits in 15 fungal isolates from a Mediterranean Southern California grassland. We inoculated fungi onto sterilized litter that was incubated at three moisture levels (4, 27, and 50% water holding capacity). For each isolate, we characterized traits that described three potential lifestyles within the newly proposed “YAS” framework: growth yield, resource acquisition, and stress tolerance. Specifically, we measured fungal hyphal length per unit litter decomposition for growth yield; the potential activities of the extracellular enzymes cellobiohydrolase, β-glucosidase, β-xylosidase, and N-acetyl-β-D-glucosaminidase for resource acquisition; and ability to grow in drought versus higher moisture levels for drought stress tolerance. Although we had hypothesized that evolutionary and physiological trade-offs would elicit negative relationships among traits, we found no supporting evidence for this hypothesis. Across isolates, growth yield, drought stress tolerance, and extracellular enzyme activities were not significantly related to each other. Thus, it is possible that drought-induced shifts in fungal community composition may not necessarily lead to changes in fungal biomass or decomposer ability in this arid grassland.